From Decline to Renewal? Understanding Children’s Relationship With Nature in the Wake of Covid-19 - Daniel Kaplan (Urban Planning)
The pandemic has significantly interrupted the already declining relationship between children and nature in recent decades. Despite the widely recognised benefits of contact with nature for general well-being, efforts to improve this relationship and reconnect children with nature have been unsuccessful so far. Although the pandemic may have represented a kind of new opportunity to restart that relationship, several studies indicated a growing gap between those who regularly engage with nature and those who do not, a gap that has been exacerbated by the pandemic. This case study investigates how children perceive their contact with nature before, during, and after the pandemic, and explores its meaning. Participants, aged between 11 and 16 years old, were recruited from schools in both rural and urban areas of Czechia and completed an online questionnaire (n = 123), followed by online group interviews with those who consented. Descriptive analysis was used to analyse quantitative data, and later thematic analysis provided insight into open-ended questions and qualitative data from interviews (n = 20). Results showed that participants spent less time in nature now than they did during the pandemic, although they acknowledged the importance of nature. A commonly cited barrier to spending more time in nature is lack of free time. The overall accessibility and quality of nature in the neighbourhood influenced participants’ time spent in and interactions with nature. Although they perceived some benefits, participants were reluctant to use virtual nature because of concerns about reduced contact with real nature and the accessibility of technical equipment. These findings provide valuable insights for local government to address issues such as accessible nature and the quality of natural areas in relation to the relationship between children and nature in the younger population. By creating such an environment, local authorities could improve the impact of nature as a resource for promoting children’s mental and emotional well-being.